Strong damping of the localized surface plasmon resonance of Ag nanoparticles by Ag2O. (16th May 2018) - Wu, Qingmen; Si, Mengting; Zhang, Bing; Zhang, Kang; Li, Huanhuan; Mi, Longfei; Jiang, Yang; Rong, Yan; Chen, Junling; Fang, Yingcui
Abstract: By studying oxidation of AgNPs (Ag nanoparticles) and decomposition of the produced silver oxide, we demonstrate that the localized surface plasmon resonance (LSPR) of AgNPs was damped by Ag2 O produced during oxygen plasma irradiation (OPI). The AgNPs were fabricated by evaporation of high pure silver under high vacuum. The oxidation was conducted in oxygen plasma generated by radio frequency glow discharging in vacuum, and the decomposition was performed by annealing the silver oxide in nitrogen ambient at temperatures ranging from room temperature to 450 °C. Samples were characterized by color, absorption spectra, surface enhanced Raman scattering, x-ray photoelectron spectroscopy, and field emission scanning electron microscopy. The bandgap of the silver oxide was calculated. We propose that AgNPs are only partially oxidized into silver oxide during OPI, and the LSPR of the AgNPs left without being oxidation is strongly damped by the produced silver oxide. This LSPR damping is responsible for the transparency of the sample after OPI for 2 s.